The Langmuir probe modeling in ion-beam plasma - Antonova, T.N.; Dudin, S.V.; Farenik, V.I. (Вопросы атомной науки и техники, 2003)
The mathematical model of single cylindrical Langmuir probe describing dependence of ion current gathered by the probe on the basic parameters of ion-beam plasma, such as probe potential, cold and beam ion densities, relation between ion and electron temperatures is built. The model covers wide parameters range of the ion-beam plasma, particularly the whole range typical for technological ion-beam systems. The results of numerical calculations are presented for the probe current versus probe dimensions and potential as well as the plasma parameters. The analytical expression for the ion current (modification of the Bohm formula) is derived for the large probe limit. For the numerical results the approximation formula is constructed, simplifying practical usage of the results. Побудовано математичну модель, що описує взаємозв'язок струму холодних іонів, що збирається зондом Ленгмюра в іонно пучковій плазмі (ІПП) з основними параметрами ІПП, такими як потенціал зонда, щільність іонів пучку і холодних іонів, співвідношення іонної і електронної температур. Модель перекриває широку область параметрів ІПП, зокрема, весь діапазон, характерний для технологічних іонно-променевих систем. Подано результати чисельних розрахунків зондового струму в залежності від геометричних розмірів і потенціалу зонда, а також від параметрів плазми. Знайдене аналітичний вираз для струму іонів в ІПП у випадку великого зонда - аналог відомої формули Бома. Для чисельних результатів побудовано апроксимаційну формулу, що дозволяє практично використовувати результати моделювання. Построена математическая модель, описывающая взаимосвязь тока холодных ионов, собираемого зондом Ленгмюра в ионно–пучковой плазме (ИПП) с основными параметрами ИПП, такими как потенциал зонда, плотность ионов пучка и холодных ионов, соотношение ионной и электронной температур. Модель перекрывает широкую область параметров ИПП, в частности, весь диапазон, характерный для технологических ионно-лучевых систем. Представлены результаты численных расчетов зондового тока в зависимости от геометрических размеров и потенциала зонда, а также от параметров плазмы. Найдено аналитическое выражение для тока ионов в ИПП в пределе большого зонда – аналог известной формулы Бома. Для численных результатов построена аппроксимационная формула, позволяющая практически использовать результаты моделирования.